Towards common ground and trading zones in management research and practice - Romme, Abel G; Avenier, Marie-José; Denyer, David; Hodgkinson, Gerard P; Pandza, Krsto; Starkey, Ken; Worren, Nicolay (British journal of management, 2015)
The purpose and nature of management scholarship is contested, evidenced by debates about the ‘academic–practitioner divide’ and attendant remedies for addressing it, including mode 2 and mode 3 research, engaged scholarship, evidence‐based management and design science. In this paper the authors argue that, without a culture of dialogical encounter, management scholarship will never be able to emerge from its adolescence, and management will not develop into the profession that it should and can become. The central proposition is that the highly fragmented landscape of management (practice and scholarship) lacks sufficient capability for dialogue among the plurality of actors situated across that landscape. Developing the dialogical capability ultimately required to break this fundamental impasse demands, first, a shared sense of purpose and responsibility (akin to the Hippocratic Oath in medicine) and, second, institutional entrepreneurship to establish more and better ‘trading zones’. Drawing on the philosophy of pragmatism, the authors further this endeavour by identifying and proposing key elements of a statement of shared purpose and responsibility. Finally, they explore the nature and characteristics of successful trading zones, highlighting particular examples that have already been created in management studies.